PENGARUH DISIPLIN KERJA & KOMPENSASI TERHADAP KINERJA PEGAWAI UP45 DENGAN KOMITMEN PEGAWAI SEBAGAI VARIABEL INTERVENING - Hartanti Widayani; Nur Widiastuti (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2026)
This study aims to analyze the influence of work discipline and compensation on employee performance at Universitas Proklamasi 45 with employee commitment as an intervening variable. This study uses a quantitative approach with a survey method through the distribution of questionnaires. The sampling technique used is purposive sampling with a total of 94 respondents from Universitas Proklamasi 45. Data analysis was carried out using the SmartPLS application to test the role of employee commitment in mediating the relationship between work discipline and compensation on performance. The results of the study indicate that: (1) Work discipline has a positive and significant effect on employee performance, (2) Compensation has a positive and significant effect on employee performance, (3) Employee commitment has a positive and significant effect on employee performance, (4) Employee commitment has a positive and significant effect on work discipline with employee performance, (5) Employee commitment has a positive and significant effect on compensation with employee performance. These findings provide new contributions in human resource management in the university environment by emphasizing the importance of work commitment as a link between discipline and compensation policies with increasing employee performance.